2020
DOI: 10.1016/j.jsv.2019.115047
|View full text |Cite
|
Sign up to set email alerts
|

Response analysis of an accelerating unbalanced rotating system with both random and interval variables

Abstract: This paper investigates the accelerating up transient vibrations of a rotor system under both the random and uncertain-but-bounded uncertainties. The Polynomial Chaos Expansion (PCE) coupled with the Chebyshev surrogate method is used to analyses the propagations of the two categorizes of uncertainties. The output responses will possess the characteristics of both bounded quantities and statistical moments. As a hybrid non-intrusive uncertainty quantification (UQ) procedure, the deterministic rotor model is ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…The temperature dependency of material properties given by Touloukian [41] can be expressed as a non-linear function of temperature, as shown in Equation (2). Although there are many other non-linear variations in the rotating systems [42,43], the non-linear gradation of material properties and non-linear temperature distribution are considered in the present work.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature dependency of material properties given by Touloukian [41] can be expressed as a non-linear function of temperature, as shown in Equation (2). Although there are many other non-linear variations in the rotating systems [42,43], the non-linear gradation of material properties and non-linear temperature distribution are considered in the present work.…”
Section: Methodsmentioning
confidence: 99%
“…As a comparison to other methods dealing with uncertainty models for instance combined hybrid uncertainty model proposed in [36] we have the following arguments. The approach in [36] is based on propagation of uncertainty (the sensitivity analysis) and mainly focuses on the classical interval arithmetic rather than providing direct (less/more conservative) solutions, see Equation (15) in [36]. Although, the Contamination model is another Hybrid or even called Mixed Model to contaminate non-probabilistic with probabilistic models via choosing proper tuning factor ( ).…”
Section: Comparisonmentioning
confidence: 99%
“…Bit-induced vibrations originate from the bit-rock cutting process, while string-induced vibrations are caused by the contact between drilling tools and formation [5]. The bit rock interaction during drilling is a complex process with many uncertainties [6], which can be considered, in various ways, e.g., with hybrid uncertainties [7]. It has been shown that, for the torsional dynamic of the drill string, the energy input can be modeled using a nonlinear torque characteristic at the bit [8].…”
Section: Introductionmentioning
confidence: 99%